Next door to the Lion King - Fridolin, David (2014)
Wildlife viewing safari ecotourism in African reserves and parks is a popular form of recreational travel among Europeans and Americans. This phenomenon means a welcome inflow of foreign currency for poor African states, and is supported by an abundance of Western conservation NGOs. This thesis explores the phenomenon of wildlife conservation from the standpoint of rural communities neighboring these protected areas. Through an interview-based field study in six villages close to the Grumeti Game Reserve in northern Tanzania, I will attempt to shed light on how the locals view and cope with the game reserve, and how it integrates with their livelihoods and practices. Some research has already been done on the subject, which I will connect my results to, in order to make sense of the material. In addition, the thesis contains a broad discussion on the incentives of nature and wildlife conservation in Africa as a postcolonial phenomenon, largely governed by the postindustrial Western ideal of a pristine African wilderness, and of nature in general as something inherently separate from human society.